PERTUMBUHAN, HASIL DAN POTENSI SERAPAN KARBONDIOKSIDA BAWANG DAYAK (Eleuteherine americana Merr) PADA TANAH GAMBUT - Sih Winarti; Alpian Alpian; Herry Palangka Jaya (Agric, 2022)
The purpose of this study was to determine the growth, yield and the potential for carbondioxide absorption of dayak onion plants given four types of manure on peat soil. This experiment used a completely randomized design with four treatments and six replications. The treatments tried were chicken, swallow, cow, goat manure. The results showed that the type of manure had an effect on plant growth and yield. The growth of plant height and the number of leaves dayak onion planted on peat soil given cow and goat manure grew significantly higher and more the number of leaves, the lowest was found in dayak onion plants fed with swallow manure. The highest yield was obtained on dayak onion plants fertilized with 30 t ha-1 cow manure with a tuber weight of 41.50 g clump-1, with a larger tuber diameter, but the highest number of tubers was obtained in dayak onion plants fertilized by swallow manure with tubers diameter smaller. The highest weight of biomass, stored carbon and carbon dioxide absorption were 6.6; 3.3 and 12.11 t ha-1 found in dayak onion plants planted on peat soil given cow manure 30 t ha-1